PENGARUH KEBIJAKAN DIVIDEN, LIKUIDITAS, SOLVABILITAS DAN EARNING PER SHARE TERHADAP HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - PUTRI JESICA SITORUS (LP2MTBM MAKARIOZ, 2020)
The purpose of this research is to test and analyze the influence of factors such as Dividend Policy, Liquidity, Solvency andEarning Per Share partially and simultaneously to share price with Return On Asset (ROA) as moderating variable. Thisresearch type is research of causal research (causal research) by using secondary data. The population in this study are allFood and Beverages companies listed in Indonesia Stock Exchange in 2012-2015, amounting to 15 companies. From thepopulation, the researcher used the entire population to be the research data (sample) in this study as many as 14companies eliminated 1 because it is still newly listed on the Indonesia Stock Exchange. So the observation data amountedto 56 observations. Data were processed using Multiple Regression Analysis and for moderating variable by using residualtest. The results of this study prove that partially debt to equity ratio has a significant negative effect and earnings per sharehave a significant positive effect on the change of KAP, while dividend payout ratio and current ratio has no significant effecton stock price. Simultaneously the dividend payout ratio, current ratio, debt to equity ratio and earnings per share have asignificant positive effect on the change of KAP. Return On Asset (ROA) is not as a moderating variable between dividendpayout ratio, current ratio, debt to equity ratio and earnings per share with stock price.